Emission of styrene from polystyrene foam and of cyclopentane from polyurethane foam - measurements and modelling - Choczyński, M.; Krajewska, B.; Stęgowski, Z.; Nęcki, J. (Polimery, 2011)
Due to toxicity of volatile organic compounds (VOC), assessment of their emission from polymer dry construction materials is of importance for the quality of the indoor environment. Accordingly, in this work we studied emissions of styrene from polystyrene foam (PSf) and of cyclopentane from polyurethane foam (PURf). Both foams are common insulation materials. The partition (K) and diffusion (D) coefficients of these compounds in respective foams were determined at temperature between 23-90 °C. The partition coefficients of foam-ambient gas system (KM-A) derived from the determined adsorption and desorption rate constants (kads, kdes) using the close-to-equilibrium theory and computer simulation, resulting in comparable values. The diffusion coefficients, by contrast, were obtained using three models based on sorption (DS), permeation (DP) and computer simulation (DC). In the first model, the foam is seen as a continuous phase, in the second model - as consisting of two phases where the VOC concentration is arithmetically averaged, while the third one assumes the inhomogeneous VOC distribution. Based on the same experimental data, three sets of diffusion coefficients were obtained (DS, DP, DC), disparate in values, these disparities originating from the assumptions made in each model. The computer-simulation at relatively low migrant concentrations in the foam (styrene-PSf system), and the permeation model at high migrant concentrations (cyclopentane-PURf system) generated the diffusion coefficients comparable with results presented in the literature.